PERANCANGAN IDENTITAS VISUAL DOEL SUMBANG SEBAGAI BAGIAN DARI REBRANDING - Indika Tukhfiyana Anwar; Aditya Januarsa (Jurnal Riset Multidisiplin Edukasi, 2025)
Doel Sumbang is a musician from Bandung who is known for his humorous, critical, and socially meaningful lyrics, with works that reflect the lives of Sundanese society and culture since the 1980s. This is what makes Doel Sumbang worthy of being called a timeless musician. This design aims to create a visual identity to build and reintroduce the image of Doel Sumbang, especially to the younger generation. The data search process was carried out using the method of direct interviews with listeners of Doel Sumbang's works from the past to the present, also conducting observations by watching several podcasts on Youtube that broadcast interviews with Doel Sumbang and supported by questionnaires to the public and literature studies in order to obtain results that are in accordance with what is to be conveyed. Based on the results of interviews conducted with Doel Sumbang listeners, they are less fond of the visual aspect, especially their Instagram account, because it is very unfortunate that the big name of Doel Sumbang is not accompanied by a consistent visual identity, therefore a visual identity is needed with the hope of encouraging the development of the Sundanese pop industry so that it continues to exist and be known through a strong, relevant, and simple visual communication approach supported by a new visual identity along with a graphic standard guidebook, Instagram posts, and also releasing merchandise.